20.20.17 problem 17

Internal problem ID [3907]
Book : Differential equations and linear algebra, Stephen W. Goode and Scott A Annin. Fourth edition, 2015
Section : Chapter 9, First order linear systems. Section 9.11 (Chapter review), page 665
Problem number : 17
Date solved : Monday, January 27, 2025 at 08:04:21 AM
CAS classification : system_of_ODEs

\begin{align*} \frac {d}{d t}x_{1} \left (t \right )&=-7 x_{1} \left (t \right )-6 x_{2} \left (t \right )-7 x_{3} \left (t \right )\\ \frac {d}{d t}x_{2} \left (t \right )&=-3 x_{1} \left (t \right )-3 x_{2} \left (t \right )-3 x_{3} \left (t \right )\\ \frac {d}{d t}x_{3} \left (t \right )&=7 x_{1} \left (t \right )+6 x_{2} \left (t \right )+7 x_{3} \left (t \right ) \end{align*}

Solution by Maple

Time used: 0.044 (sec). Leaf size: 48

dsolve([diff(x__1(t),t)=-7*x__1(t)-6*x__2(t)-7*x__3(t),diff(x__2(t),t)=-3*x__1(t)-3*x__2(t)-3*x__3(t),diff(x__3(t),t)=7*x__1(t)+6*x__2(t)+7*x__3(t)],singsol=all)
 
\begin{align*} x_{1} \left (t \right ) &= c_{1} +c_{2} t +c_3 \,{\mathrm e}^{-3 t} \\ x_{2} \left (t \right ) &= \frac {c_3 \,{\mathrm e}^{-3 t}}{2}+c_{2} \\ x_{3} \left (t \right ) &= -c_{2} -c_3 \,{\mathrm e}^{-3 t}-c_{1} -c_{2} t \\ \end{align*}

Solution by Mathematica

Time used: 0.009 (sec). Leaf size: 136

DSolve[{D[x1[t],t]==-7*x1[t]-6*x2[t]-7*x3[t],D[x2[t],t]==-3*x1[t]-3*x2[t]-3*x3[t],D[x3[t],t]==7*x1[t]+6*x2[t]+7*x3[t]},{x1[t],x2[t],x3[t]},t,IncludeSingularSolutions -> True]
 
\begin{align*} \text {x1}(t)\to e^{-3 t} \left (-\left (c_1 \left (e^{3 t} (t+1)-2\right )\right )-2 c_2 \left (e^{3 t}-1\right )-c_3 \left (e^{3 t} (t+2)-2\right )\right ) \\ \text {x2}(t)\to e^{-3 t} \left (c_1 \left (-e^{3 t}\right )-c_3 e^{3 t}+c_1+c_2+c_3\right ) \\ \text {x3}(t)\to e^{-3 t} \left (c_1 \left (e^{3 t} (t+2)-2\right )+2 c_2 \left (e^{3 t}-1\right )+c_3 \left (e^{3 t} (t+3)-2\right )\right ) \\ \end{align*}